Derivation of interface features for user-centric information retrieval systems. - Lee, Shu Shing. (2010)
As information resources become widely accessible, it becomes crucial that users’ needs are investigated to design user-centred information retrieval (IR) interfaces that help users identify appropriate documents. Yet, most IR systems retrieve relevant documents by matching queries to documents. This system-oriented measure of relevance does not meet users’ view of relevance where documents are assessed by subjective relevance based on how useful documents are for addressing users’ individual tasks.